2014
DOI: 10.1163/22134913-00002021
|View full text |Cite
|
Sign up to set email alerts
|

Polygon-Based Drawing Accuracy Analysis and Positive/Negative Space

Abstract: The study of drawing generally depends on ratings by human critics and self-reported expertise of the drawers. To complement those approaches, we developed an objective continuous performance-based measure of drawing accuracy. This measure represents drawings as sets of landmark points and analyses features of particular research interest by comparing polygons of those features’ landmark points with their counterpart polygons in a veridical image. This approach produces local accuracy measures (for each polygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This suggests that the development of artistic expertise involves an ability to see familiar object and scenes as if they were unfamiliar, in order to reduce the influence of biasing categorical schemas. In support of this contention, Carson, Millard, Quehl and Danckert (2014) found that the orientation of negative space (the space between objects or elements of the visual scene) is drawn more accurately than regions of (identifiable) positive space, while the proportionality of positive space is drawn more accurately than negative space ( Figure 5). The effect of familiarity on drawing errors may be due to the fact that familiar objects and their relations are coded categorically when being rendered.…”
Section: Negative Categorical Schemasmentioning
confidence: 80%
“…This suggests that the development of artistic expertise involves an ability to see familiar object and scenes as if they were unfamiliar, in order to reduce the influence of biasing categorical schemas. In support of this contention, Carson, Millard, Quehl and Danckert (2014) found that the orientation of negative space (the space between objects or elements of the visual scene) is drawn more accurately than regions of (identifiable) positive space, while the proportionality of positive space is drawn more accurately than negative space ( Figure 5). The effect of familiarity on drawing errors may be due to the fact that familiar objects and their relations are coded categorically when being rendered.…”
Section: Negative Categorical Schemasmentioning
confidence: 80%
“…One of the common strategies used by artists (Chamberlain, 2012) and recommended by teachers (Edwards, 1989, p. 97; Mendelowitz et al, 2007, p. 50) is to attend to the negative space, that is, the shapes of the meaningless regions between foreground objects. Carson et al (2014) demonstrated that the pattern of drawing errors does indeed differ significantly between shapes in the positive and the negative space, the meaningful and the meaningless.…”
Section: Discussionmentioning
confidence: 96%
“…To produce objective measures of drawing accuracy, the GT photographs and drawings were manually annotated using a Matlab script to locate unambiguous landmarks for geometric analysis. We conducted a geometric analysis of drawing accuracy using an approach that has been reported previously (Carson et al, 2014). For information, we summarize the method here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation